POPULASI DAN SERANGAN Cnaphalocrosis medinalis (LEPIDOPTERA; PYRALIDAE) PADA TANAMAN PADI SAWAH DI KABUPATEN MINAHASA TENGGARA - Dien, Moulwy F.; Kandowangko, Daisy S. (EUGENIA, 2017)
ABSTRACTThe experiment was conducted using a survey method at 4 locations/district in the Southeast Minahasa Regency is Belang,Tombatu, North Tombatu, and East Tombatu. Each location/districts determined three paddy fields (repeats) as a place of observation and sampling. The study lasted for 10 months ie from January to October 2015. Sampling is done diagonally to the respective fields. So one rice field consists of 5 sub-plot as a point of sampling Samples are larvae present in the leaf roll. Implementation of the sampling carried out on rice plants vegetative phase once a week for 6 weeks. The results showed that the average population of C. medinalis (per-10 clumps) on paddy rice cultivation in Southeast Minahasa Regency highest found in the location of the North Tombatu 10.99, then Eastern Tombatu 10.44, Belang 10.43 and lows in the Tombatu 0.94. Observations of percentage of pests C. medinalis highest in Southeast Minahasa Regency found in the sample locations in the North Tombatu which reached 33.95%, Belang 32.51%, Eastern Tombatu 31.86%, and the lowest in the Tombatu 4.08%. Keywords : rice, Cnaphalocrosis medinalis